Classification Of Modern Ecological Problems and Principles of Forming Ecological Competence in Students (Web of Technology: Multidimensional Research Journal, 2023)
Today, the demand for information about environmental changes that are causing a lot of discussion in our society, which are happening around us, as well as the whole world, is increasing every day. This article will show with scientific reviews and specific figures the impact of the human factor on modern environmental problems and the solution of problems, a brief analysis of the environmental problems observed in the world stage and Uzbekistan at present.